Outcomes of Tubeless Percutaneous Nephrolithotomy in Patients With Chronic Renal Insufficiency (Iranian Journal of Kidney Diseases, 2012)
We evaluated the outcomes of percutaneous nephrolithotomy in patients with chronic renal insufficiency. A total of 60 patients with a creatinine level greater than 1.5 mg/dL who underwent PCNL were included. Serum creatinine level, as a kidney function index, was assessed before and after the operation. The mean calculus size was 31.13 ± 9.38 mm. The mean pre-operative and 2-week postoperative serum creatinine levels were 2.43 ± 0.75 mg/dL and 2.08 ± 0.78 mg/dL, respectively. There was a significant difference between the pre-operative and postoperative creatinine levels in all postoperative days (days 1, 2, and 14). Fifty of the 60 patients (83.3%) were stone free. Ten patients (16.6%) developed postoperative fever. We can conclude that percutaneous nephrolithotomy seems to be a safe and effective therapeutic option for kidney calculi in patients with chronic kidney disease.